Russia: Inadequate Priority Given to Energy Efficiency and Climate Protection - Hella Engerer; Claudia Kemfert (Weekly Report, 2008)
Russian energy production has increased substantially in recent years, with production of natural gas now actually exceeding the levels reached in the early 1990s. The growth in energy production has gone hand in hand with a rise in Russian energy exports. The European Union is an extremely important sales area for Russia. Vice versa, energy deliveries from Russia account for a very sizable share of all energy supplies to Europe and Germany. Russia insists that it can continue to guarantee a stable supply of energy to Europe in the future. The energy strategy pursued in Russia foresees (similar to the energy plans of the past) significant increases in production and exports of the most important energy sources - crude oil and natural gas. Natural gas exports have remained below target to date, however. If energy export growth is to be accelerated, then besides higher investment in the energy sector, measures to improve energy efficiency and thus reduce domestic consumption are also required.
Keywords: Q4; Q43; P28; 330; Energy policy in Russia; Energy efficiency; Climate policy in Russia